2020
DOI: 10.1371/journal.pone.0215113
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of lactic acid bacteria capable of reducing environmental alkyl and fatty acid hydroperoxides, and the effect of their oral administration on oxidative-stressed nematodes and rats

Abstract: Reinforcement of the hydroperoxide-eliminating activity in the small and large intestines should prevent associated diseases. We previously isolated a lactic acid bacterium, Pediococcus pentosaceus Be1 that facilitates a 2-electron reduction of hydrogen peroxide to water. In this study, we successfully isolated an alternative lactic acid bacterium, Lactobacillus plantarum P1-2, that can efficiently reduce environmental alkyl hydroperoxides and fatty acid hydroperoxides to their corresponding hydroxyl derivativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…This reduction in the TBARS and GSH markers could have protective effects against inflammation. Similar results reported by Watanabe et al, 2020 [57] as concluded the effective of L. plantarum P1-2 and P. pentosaceus Be1 for reducing oxidative stresses in vivo.…”
Section: Plos Onesupporting
confidence: 89%
“…This reduction in the TBARS and GSH markers could have protective effects against inflammation. Similar results reported by Watanabe et al, 2020 [57] as concluded the effective of L. plantarum P1-2 and P. pentosaceus Be1 for reducing oxidative stresses in vivo.…”
Section: Plos Onesupporting
confidence: 89%
“…Since LpP1-2 has potent peroxidized fatty acid reducing activity, its administration may have suppressive effect on iron toxicity. Previously, we showed that LpP1-2 must be administered as viable bacteria to exert this activity effectively [9]. The present study demonstrated its effectiveness in pigs.…”
Section: Physiological Effectsupporting
confidence: 65%
“…Previously, a decrease in lipid peroxidation index was observed in the colonic mucosa of ironoverloaded rats administrated with LpP1-2 [9]. In the present study, TBARS level in serum samples iron-fed piglets in the LABLp-administrated group was lower than that in the nonadministrated group.…”
Section: Physiological Effectsupporting
confidence: 51%
See 2 more Smart Citations